XPS studies of the surface of TiO2:Ag nanopowders - O. M. Korduban; T. V. Kryshchuk; V. O. Kandyba; V. V. Trachevskii (Хімія, фізика та технологія поверхні)
n-TiO2 and n-TiO2:Ag nanopowders were synthesized by the method of electric explosion of wires (EEW). The doping of nanopowders took place during the explosion of titanium wire, on the surface of which an Ag2O layer of the appropriate mass was applied. The energy of the explosion was equal to Е = 3.1·Еs, where Es is the energy of sublimation of the metal. Based on the synthesized nanopowders, mesoporous n-TiO2 and n-TiO2:Ag films were formed. The phase composition of the surface of several series of n-TiO2 and n-TiO2:Ag samples under different annealing conditions was studied by X-ray photoelectron spectroscopy. The XPS spectra of the Ti2p- and Ag3d- levels were decomposed by the Gauss-Newton method into interconnected components 2p3/2/2p1/2 and 3d5/2/3d3/2 with parameters DЕ = 5.76 eV; I1/I2 = 0.5 and DЕ = 6.0 eV; I1/I2 = 0.66 to take into account the spin-orbit splitting of the pair respectively. The paper presents histograms of the contributions of the components to the Ti2p- and Ag3d- spectra, which vary depending on the degree of doping and annealing conditions for 4 series of samples. According to XPS data, on the surface of EEW nanopowders TiO2 and TiO2:Ag titanium is represented by Ti3+- and Ti4+- states, silver by Ag0-, Ag1+- and Ag2+- states. In all series of samples, the contribution of the Ti3+- state simultaneously increases with an increase in the absolute Ag content, which is a consequence of the lattice distortion through the formation of a surface phase with Ti–O–Ag bonds. Annealing at 300 °C in air leads to an increase in the contribution to the spectra of Ti4+- states of ЕbTi2p3/2 = 458.3 eV and Ag1+ - states. Pretreatment of the samples with hydrogen peroxide before annealing leads to an increase in the contribution of oxide-hydroxide phases of titanium and Ag0- states. Annealing of the samples at 300 °С in argon with pretreatment with hydrogen peroxide leads to an increase in the contribution to the spectra of Ti4+- states with ЕbTi2p3/2 = 458.8 eV, oxide-hydroxide phases of titanium and Ag0. It has been found that the direction of redox processes on the surface of n-TiO2 after the action of H2O2 and subsequent annealing in air depends on the state of hydration of the original nanopowders.